2020
DOI: 10.3390/jcm9020471
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Testicular Disruption from Exposure to Bisphenol A and Phtalates

Abstract: Great attention has been paid in recent years to the harmful effects of various chemicals that interfere with our natural hormone balance, collectively known as endocrine-disrupting chemicals (EDCs) or endocrine disruptors. The effects on the reproductive system of bisphenol A (BPA) and phthalates have received particular attention: while they have a short half-life, they are so widespread that human exposure can be considered as continuous. Evidence is often limited to the animal model, disregarding the likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 97 publications
(116 reference statements)
0
31
0
3
Order By: Relevance
“…In general, animal models have shown that EDCs can affect Hypothalamic-Pituitary-Gonadal (HPG) axis and ovarian function, pubertal development, and trophoblast/placental function [ 16 ]. Organochlorine compounds, pesticides and estrogenic drugs have been extensively studied, but a growing amount of data are investigating the impact of compounds such as phthalate esters and phenols (and bisphenol A in particular) [ 9 ]. These are frequently found in commonly used plastic products and, despite their short half-life, human contact is so common that exposure can be considered continuous [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, animal models have shown that EDCs can affect Hypothalamic-Pituitary-Gonadal (HPG) axis and ovarian function, pubertal development, and trophoblast/placental function [ 16 ]. Organochlorine compounds, pesticides and estrogenic drugs have been extensively studied, but a growing amount of data are investigating the impact of compounds such as phthalate esters and phenols (and bisphenol A in particular) [ 9 ]. These are frequently found in commonly used plastic products and, despite their short half-life, human contact is so common that exposure can be considered continuous [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have showed that exposure to DEHP (among the most common phthalates diesters) altered sexual differentiation, inhibited androgen production, reduced testicular testosterone levels, and shortened anogenital distance (AGD) in male rats [ 9 ]. In female rats, DHEP and the monoester metabolite MEHP provoked a reduction of serum estradiol and progesterone likely mediated by inhibition of the transcription of aromatase enzyme (P450arom) that converts androgens to estrogens [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, fetal exposure to bisphenol-A, a chemical with estrogenic activity, disrupted spermatogenesis damaging viability, motility, and sperm chromatin condensation of adult mice [ 36 ]. The negative impact of this chemical on human fertility has been already ascertained [ 37 ], as well as that of phthalates [ 38 ]. Similarly, fetal exposure to cigarette smoke in mice led to a dose-dependent decrease of epididymal sperm counts both in F1 and F2 male offspring, indicating a transgenerational deleterious effect [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Різноманітні аномалії чоловічої статевої системи (наприклад, крипторхізм) та шкідливі фактори навколишнього середовища обумовлюють дисфункцію клітин Лейдіга, що в свою чергу призводить до захворювань, пов'язаних із недостатністю андрогенів [1]. Наприклад, було продемонстровано, що аналоги естрогенів, такі як бісфенол А, можуть знижувати продукцію сперматозоїдів, порушуючи функцію клітин Лейдіга і пригнічуючи секрецію тестостерону [2]. Ожиріння також може знижувати кількість клітин Лейдіга і секрецію тестостерону та погіршувати репродуктивну функцію [3].…”
Section: вступunclassified